Perbandingan Harga Plat Lantai Ruko Antara Plat Lantai Konvensional Dan Plat Lantai Steel Decking (Case Studi : Area Pekanbaru) - Andika Leneldo; Hendra Taufik (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Many flats house in the city of Pekanbaru was increased rapidly, however process is still using conventional methods. Conventional method by using formwork systemdisassembly, such as wood and plywood, so make the costs are relatively larger. In research have plan to eliminate of wood or plywood thein and the cost of implementation. composite steel decking methods used with smartdek type.The analysis was focused on the structure of plate (floor) with dimensions 4x20 meters, 5x20 meters and 6x20 meters. As a resuld, there are differances implementing cost between the conventional method and composites method. The plate withdimensions 4x20 meters consume Rp. 46,241,787 by using conventional method, - and result by composite method consume Rp. 35,873,777.for plate with dimensions 5x20meter, result analysis by conventional method consume Rp. 57,958,191 and the composite method consume Rp. 46,820,138 while the dimensions of 6x20 meters consume Rp. 69,781,416 by conventional method and Rp. 61,361,015 by composite method. The conclusion : (1). Comparison Price of structure plate between method and composites method conventional for the dimensions of 4x20 =1:1.289, the dimensions of 5x20 = 1:1,238, while for the 6x20 = 1:1,137. (2) Effectiveness comparisons price of composites and conventional floor plate (steel decking) the dimensions of 4x20 = 22.42%, plate with dimensions 5x20 = 19.22%, and for the dimensions of 6x20 = 12.07%.so result the paper more effective using composite plates.Keywords: the conventional method, the cost of implementation, composite methods, steel decking, smartdek, floor plate.